Election 2016. (2016) - (Political scientist), Aiton, Andrew; Burnside, Ross; (Head of Financial Scrutiny Unit, SPICe), Campbell, Allan; (Information officer), Edwards, Tom; Liddell, Greig; McIver, Iain, 1978-; McQuillen, Alanis
No abstract available